Harmony of Islam and Local Wisdom: An Ethnographic Study of Wetu telu Tradition in Lombok - Raden Sumiadi (Universitas Islam Negeri Madura, 2025)
This research examines the socio-cultural negotiation processes that facilitate accommodation between Islam and indigenous customs in the learning practices of the Wetu telu community in Bayan, North Lombok. Using a qualitative ethnographic approach, this study examines how the Wetu telu indigenous community negotiates Islamic values with local wisdom, strategies employed by internal community actors in accommodating Islamic implementation, and the development of a contextual Islamic model that respects local wisdom while maintaining Islamic authenticity. The findings reveal three main strategic approaches: (1) elite power approach through structural negotiation with traditional leaders, (2) emotional approach through relationship building and interpersonal trust, and (3) cultural approach through integration of Islamic teachings into local traditions without negating cultural identity. This research produces a multidimensional accommodation model that enables the integration of Islamic values within indigenous social systems while maintaining cultural integrity. The resulting framework demonstrates that effective Islamic implementation in indigenous communities requires recognition of existing cultural knowledge systems and integration of religious teachings within traditional learning processes. This model provides a practical framework for developing contextual Islamic integration that can be applied in other regions with similar characteristics, emphasizing the role of internal community actors as primary agents of change who ensure religious transformation emerges from within existing social structures.